2020
DOI: 10.12701/yujm.2019.00388
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous ileal inflammatory fibroid polyp and Meckel’s diverticulum found during laparoscopic surgery for adult intussusception

Abstract: We present a rare case of synchronous ileal inflammatory fibroid polyp and Meckel's diverticulum detected during laparoscopic surgery for adult intussusception. A 48-year-old woman presented with sudden onset of severe abdominal pain. Abdominal computed tomography revealed a segment of ileocecal intussusception. Thus, laparoscopic exploration was performed, which revealed an ileal mass with an outpouching closed luminal structure in the distal ileum. Two abnormal structures were resected via mini-laparotomy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Two patients were less than 6 months of age, ( 6 , 10 ) three between 1 and 6 years of age, ( 14 , 16 , 17 ) five between 15 and 30 years of age ( 5 , 7 , 13 , 18 , 19 ) and five between 40 and 50 years of age. ( 8 , 9 , 11 , 12 , 15 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two patients were less than 6 months of age, ( 6 , 10 ) three between 1 and 6 years of age, ( 14 , 16 , 17 ) five between 15 and 30 years of age ( 5 , 7 , 13 , 18 , 19 ) and five between 40 and 50 years of age. ( 8 , 9 , 11 , 12 , 15 )…”
Section: Discussionmentioning
confidence: 99%
“…From a geographical perspective, we observed that 15 publications came from five continents. One was from America (United States), (5) four from Europe (Italy, (6) France, (7) Spain (8) and the United Kingdom), (9) one from Africa (Tunisia), (10) seven from Asia (Japan, (11)(12)(13)(14) South Korea, (15) China (16) and Syria) (17) and two from Oceania (Australia). (18,19) Regarding the age of the patients included in this sample, there was a range from newborns to 49 years of age.…”
Section: Epidemiologymentioning
confidence: 99%
“…This study indicated that surgery is the predominant treatment for intussusception in adults. In some cases, laparoscopy is a useful adjunct to open surgical techniques ( Kang & Gu, 2020 ). Although laparotomy or laparoscopic enterectomy is the ideal method, cases using laparoscopic techniques have no postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…This case report analyzes a rare circumstance of intussusception caused by a fibroid polyp. Less than 100 cases of intussusception secondary to ileal polyp are described in the literature (12). An inflammatory fibroid polyp (IFP), also called Vanek's tumor, is a benign submucosal tumor frequently localized in the stomach, especially in the antrum, but it can occur throughout the gastrointestinal tract ( 13).…”
Section: Discussionmentioning
confidence: 99%